ASSESSMENT OF GOOD CORPORATE GOVERNANCE IMPLEMENTATION IN PT PERKEBUNAN NUSANTARA III (PERSERO) - Arif, Syaiful (Dinasti International Journal of Digital Business Management, 2020)
The research carried out at PT Perkebunan Nusantara III (Persero) aims to find out how the implementation of Good Corporate Governance and what obstacles are encountered in its implementation. The results of the study stated that PT Perkebunan Nusantara III (Persero) received an excellent rating based on the assessment. The implementation of Good Corporate Governance in the company is demonstrated by the implementation of the principles of Good Corporate Governance, namely the principle of Openness with transparency regarding the appointment process of the Directors through due diligence and compliance, the principle of Accountability with clarity of functions and responsibilities of corporate organs through the organizational structure, the principle of Responsibility for the existence of the program corporate social responsibility, the Independent principle by setting an independent auditor the Public Accountant Office to audit the financial statements and finally the Fairness principle is indicated by the existence of different regulations regarding company management. As for the obstacles faced, there is no transparency in the process of selecting members of the Board of Commissioners, the reward and punishment system has not been implemented by the company, the minutes of the meeting have not met the dynamics of the meeting, not yet published.